Prevalence and Morphometric Analysis of Double Mental Foramen and Double Mandibular Foramen from Digital Panoramic Radiographs - Farfán,Constanza (Sociedad Chilena de Anatomía, 2020)
SUMMARY: The morphological variations of the mental foramen (MF) and mandibular foramen (MBF) have been studied for several years, and the prevalence and morphometric characteristics of double and triple foramina have been reported. The objective of this study was to establish the prevalence of variations in the MF and MBF, and to carry out a morphometric analysis of a Chilean population using digital panoramic radiographs. The study included 927 radiographs; the observed prevalence of double MF was 2.58 %, while the prevalence of double MBF was 1.51 %. No cases of triple foramina were found. In men, double MF was found more frequently in the left hemiarch (64.28 % of cases), while in women it was more frequent in the right hemiarch (80 %). Double MBF was found more frequently in the right hemiarch in women (80 % of cases), while the distribution between left and right in men was even. The mean area, width and height of the double MF were 5.46 mm2, 2.77 mm and 2.57 mm respectively. The means of the same morphometric measurements in double MBF were 6.37 mm2, 2.27 mm and 3.19 mm respectively. In both foramina, statistically significant differences were only found between the height of the foramen and the age of the subjects, with the observation that the greater the subject's age, the smaller the height. Dental surgeons must take these anatomical variants into consideration in clinical and surgical actions; timely diagnosis by radiograph is important to avoid possible complications.